Performance of laser assisted micro-milling (laμmill) of titanium alloy using micro ball end mill - Mohid, Zazuli (2018)
Laser assisted milling technique turns to be complicated and unpredictable when the machining size is scaled to micro level. Furthermore, less has been reported on the application of ball end mill in laser assisted micro milling. This study was carried out to evaluate and clarify the machining characteristics of micro ball end mill in laser assisted micro milling of titanium alloy Ti6Al4V. Finite element method (FEM) simulation of preheating was used to determine the machining parameters and the cutting tool to laser beam distance. The performance of laser assisted micro milling using micro ball end mill was evaluated via experimental works using various feed, feed rate, depth of cut and cutting speed. The cutting force, tool wear, chip pattern, burr and machining surface conditions were compared between conventional micro milling and laser assisted micro milling. Machining simulation was also carried out to study and collect the supportive evidence to explain the chips formation mechanisms. The laser heating simulation model was built and validated to determine the cutting tool to laser beam distance. When the feed rates ranging from 52.5 to 210 mm/min, the workpiece temperature at machining region was increased from 128 °C to 178 °C when the cutting tool is located at 0.6 mm from the laser. At this condition, the creation of heat affected zone and melted zone were successfully avoided. This study has proven that laser assisted micro milling reduces the cutting force approximately 5 to 20 %, depending on the feed and depth of cut applied. However, it is also found out that the chip pattern has a strong correlation with tool wear rate and surface roughness. It was observed that loose arc chips were produced at the feed and depth of cut of 3.0 x 10-3 mm/flute and 0.02 mm, respectively. This type of chip is preferable due to less chip blocking, rubbing and chip compression effect. It is also proven that laser assisted micro milling technique is more effective when the workpiece temperature is increased to approximately 250 °C compared to 180 °C.